Analisis nilai karakter cerita legenda dalam buku siswa kelas iv sd tema 8 “daerah tempat tinggalku” kurikulum 2013 - Wiji Istari; Retno Winarni; Anesa Surya (Universitas Sebelas Maret, 2021)
This research was conducted for describing the value of the character in the legend story in the fourth grade students book theme 8